Religious and spiritual motifs in the art of the patients of Nikkilä Hospital - Kuuva, Sari (Approaching Religion, 2021)
This article focuses on religiousness and spirituality in the art works of psychiatric patients of Nikkilä Hospital, Finland. The pictures analysed here belong to a collection held at the Helsinki City Museum and they were made during the twentieth century. The theoretical frame of the study is a cultural study of mental health. The collection is approached as presenting a specific kind of imagery which has connections not only to the personal history and diagnoses of the patients; their cultural context and hospital environment is also taken into account. The religiousness and spirituality of the Nikkilä collection are also compared with outsider art and examples of art history internationally.